ASSESMENT OF CONSUMER AWARENESS ABOUT USAGE OF FOOD LABELS AND ITS IMPACT ON FOOD BUYING BEHAVIOUR - Pal Kaur, Virender; Kaur, Nirmal; Qumar, Neha (International Journal of Research -GRANTHAALAYAH, 2016)
Food labeling enables consumers to make informed decisions when purchasing and consuming food products. Consumption of packaged food items has grown tremendously in the recent past. Despite this, the issue of consumer awareness about usage of food labeling information has attracted little research attention in developing countries. Food regulations and increased consumer awareness are forcing packaged food companies across the world to display more and more information on packaged food products. However, little is known about consumer response to such information in emerging economies. For this the data was collected with the help of interview schedule conducted amongst 60 respondents out of which 30 were male and 30 were females from higher education institutes of Pilibhit District of Uttar Pradesh. The study assesses the level of awareness about different categories of information generally displayed on food labels. The study also examines the usage of food labels information during purchase decisions of the respondents about packaged food. All 60 subjects had knowledge about food labels. Amongst male respondents 56.66 per cent were those who purchased packaged food more than once a week, 16.66 per cent purchased it once a week, 6.66 per cent purchased it once a month and 20 per cent purchased it occasionally which is quite similar as females. Gender was significantly associated with the frequency of buying packaged foods and reading food label. The usage of the information printed on packaged food was relatively high amongst the consumers while buying packaged food products. Despite a high frequency of purchasing packaged foods, the percentage of males and females reading food labels and components of food labels on a regular basis was found very less. It is found that consumers in these three education institutes were fairly aware about the information provided on the food labels; though the level of awareness about different types of information varied. The results indicated that particular category of information was used more by the consumers while purchasing packaged food products. The results had very strong implications for researchers as well as the food companies.